2001
DOI: 10.1046/j.1365-2885.2001.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and disposition of sodium and procaine penicillin G (benzylpenicillin) administered orally with milk to calves

Abstract: Eighteen 1-week-old Holstein calves were randomly assigned to one of three groups: (a) sodium penicillin G administered intravenously, (b) sodium penicillin G administered orally, or (c) procaine penicillin G administered orally. All calves were dosed with penicillin G at 4.0 mg/kg BW. At 5 weeks of age, the calves were dosed again. Blood samples were taken serially for 24 h after both dosings. Plasma was assayed for penicillin G by high performance liquid chromatography (HPLC). For i.v. administration, the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Ranheim et al reported that the clearance of penicillin was lower in 1-week-old piglets than in adult pigs (7,51). Musser et al found that the volume of distribution at steady state (V ss ) of the calf was significantly higher than that of adult cattle (5,30). The use of adult data only may not be able to describe all of the PK characteristics of penicillin G. Thus, we combined data from a wide range of weights and ages by adding them as covariates in order to illustrate their relationships with the basic PK parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ranheim et al reported that the clearance of penicillin was lower in 1-week-old piglets than in adult pigs (7,51). Musser et al found that the volume of distribution at steady state (V ss ) of the calf was significantly higher than that of adult cattle (5,30). The use of adult data only may not be able to describe all of the PK characteristics of penicillin G. Thus, we combined data from a wide range of weights and ages by adding them as covariates in order to illustrate their relationships with the basic PK parameters.…”
Section: Discussionmentioning
confidence: 99%
“…or intramuscular (i.m.) (5,6), while penicillin G procaine is approved for use via intramuscular and subcutaneous (s.c.) administration for cattle and swine (7).…”
mentioning
confidence: 99%
“…In a study using experimental animals, administration of high dose of penicillin G is required for seizure induction (Stankiewicz et al, 1995). Additionally, the oral bioavailability of penicillin G in mammals is low (Poschet et al, 1999;Musser and Anderson, 2001). In the present study, no deaths in zebrafish larvae were observed and general symptoms were good.…”
Section: Discussionmentioning
confidence: 41%
“…The efficacy of penicillin against Sarcina is unknown, but it may be effective locally, and penicillin is safe. 2 The decision for surgery was considered to be the best option for this calf, although no studies have proven whether surgical or medical management is better for calves with abomasitis.…”
mentioning
confidence: 99%